From engagement to empowerment: integrating gamification and the Living Lab methodology into child-centered health innovation - Habibipour, Abdolrasoul (Frontiers in Digital Health, 2025)
This article presents the design, development, and field testing of Save the World, a gamified healthcare application aimed at promoting health awareness and environmental literacy among children aged 8–10 years. Developed within the Horizon Europe SynAir-G project, the application combines game-based mechanics with the iterative Living Lab (LL) methodology to foster engagement, inclusivity, and real-world learning. The app was cocreated with children, parents, teachers, healthcare professionals, and developers through a multistakeholder, cocreative process involving workshops in Sweden and Denmark. Drawing on LL principles, such as stakeholder engagement, real-life experimentation, and continuous feedback, this research enhanced the contextual relevance and usability of game features while addressing ethical considerations and diverse user needs. The field-testing results show that the integration of the gamification and LL methodologies significantly improved user engagement, educational value, and technical performance. The study demonstrates how LL and gamification can reinforce one another in creating meaningful, child-centered digital innovations, aligning with broader European goals around sustainability, digital inclusion, and participatory design.